Disrupting From Within: Teungku Inong and The Reconfiguration of Religious Authority in Aceh's Dayah - Putri Maulina; Irwan Abdullah; Wiwik Sushartami; Arifah Rahmawati (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
The participation of women ulama in Aceh has grown alongside the tightening of religious regulations. However, Southeast Asian scholarship on piety and agency rarely unpacks dayah's institutional mechanisms—especially the conversion of ethical capital into institutional recognition through negotiation and strategy within conventional (male-dominated) leadership arenas. To address this gap, drawing on qualitative data (interviews, observation, and forum documentation), this study examines: (i) the formation of piety and credentials among teungku inong; (ii) strategies for negotiating authority across compliance and resistance; and (iii) the conditions that render leadership legitimacy contingent. The findings show the cultivation of piety through a dayah–university trajectory, mastery of turāth texts and sanad networks, ritual discipline, and varied sartorial expressions; and the expansion of authority via the lexicon of musāwah, alternative spaces (beut seumeubeut and protection services), participation in formal bodies, sanad networks, and collaborations with NGOs. Overall, women's religious legitimacy in Aceh is contextual and contingent, emerging at the intersection of piety and institutional recognition, and shifting between transformation and co-optation. Keterlibatan ulama perempuan di Aceh meningkat seiring penguatan regulasi keagamaan, sementara kajian tentang kesalehan dan agensi di Asia Tenggara masih jarang mengurai mekanisme institusional dayah—khususnya konversi modal etis sebagai negosiasi dan strategi dalam arena kepemimpinan konvensional yang didominasi laki-laki. Untuk mengisi kekosongan tersebut dengan berbasis data kualitatif (wawancara, observasi, dokumentasi forum), studi ini memfokuskan pada: (i) pembentukan kesalehan dan kredensial teungku inong; (ii) strategi negosiasi otoritas antara kepatuhan dan resistensi; dan (iii) kondisi yang membuat legitimasi kepemimpinan bersifat kontingen. Temuan menunjukkan pembudayaan kesalehan melalui lintasan dayah–kampus, penguasaan kitab turāth, disiplin ritual, dan ragam ekspresi busana; perluasan otoritas lewat kosakata musāwah, ruang alternatif (beut seumeubeut dan layanan perlindungan), partisipasi di lembaga formal, jejaring sanad, dan kolaborasi LSM. Temuan menegaskan legitimasi keagamaan perempuan di Aceh bersifat kontekstual-kontingen, lahir dari persilangan kesalehan dan rekognisi kelembagaan, serta bergerak antara transformasi dan ko-optasi.